The importance of industrial visit to enhance student’s learning in process instrumentation and control unit of engineering courses - Sen, Tushar (The International academic Forum, 2013)
The objective of this plant visit is to help students gain first-hand information regarding application of instrumentation and control in process industry. In this paper the author presented the effectiveness of an industry visit in the process of learning process instrumentation and control in a 3rd year undergraduate Chemical Engineering core unit of Curtin University, Western Australia. This also demonstrated that the industrial visit is an integral part of this unit to achieve the learning outcomes. The unit is divided into lecture class, laboratory, mini-project and a site visit. Due to the large enrolment in this unit and also due to limitation of plant’s capacity, the two different plant visits was conducted by three afternoon sessions. The plants were (1) Alcoa Kwinana Refinery and (2) Coogee Chlor-Alkali Pty Ltd, Kwinana, WA. These plants were chosen because both the plants are dealing with large processes with various automatic control system and also location wise they are closer to Curtin University. Three guides from each plant explained the various process sections of plant including control room. In a week after the visit, an anonymous questionnaires survey was conducted where they were asked to put their level of agreement with statement about (i) motivation, (ii) role of process control engineer, (iii) effective unit learning through plant visit, (iv), coordination of the site visit, (v) resources and (vi) overall satisfaction. The survey results indicated that the percentage of agreement on overall learning unit outcomes through integral plant visit was 78%. The average agreement for all the items was found as 66%. The percentage agreement on all items varied from 48% to 80% which indicate overall student’s positive learning experience at the end of plant visit and this activity should be retained with the unit learning.